Simulasi Numerik Prarancangan Perpipaan LNG Circulation Line di Aliran Masuk Air Ambient Vaporizer (AAV) - Muhammad Ikhsan; Ratna Sari; Reza Fauzan (Politeknik Negeri Lhokseumawe, 2023)
The circulation process is a process to make pipes in the LNG industry always in LNG operational cryogenic temperature condition -160° C. The LNG circulation line facility on the AAV inlet pipe is expected to flow LNG continuously as a solution to keep the pipe always in a state of cryogenic temperature. The pressure drop from one point to another with lower pressure is referred to as a